PENINGKATAN KETERAMPILAN MENULIS KREATIF NASKAH DRAMA MENGGUNAKAN MEDIA FILM PADA SISWA SMP - Sutrini, Sutrini; Priyadi, A. Totok; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ Accordingly, the purpose of this study is the description of planning, execution, and learning result of creative writing drama script. The method used in this research is descriptive method, with qualitative research design of action research class (PTK). This research is conducted in 3 cycles, each cycle is done in one meeting. The research implementation procedure of each cycle consists of four stages: planning, acting, observing, and reflecting learning activities. The results of the implementation in the first cycle obtained 85.29% (excellent). Furthermore, cycle II increased with the results obtained 88.24% (excellent), and cycle III and increased by 2.89% with the results 91, 18% (excellent).Â Keywords: creative writing, drama script, film media.